PANDAS: a potential link between group A streptococcal infections and neurological disorders - Cleary, P. Patrick (Henry Stewart Talks, 2018)
The effect of Group A streptococcal infections on the behaviour of children, The problem of diagnosis in PANDAS, Potential mechanisms underlying PANDAS and the role of the immune system, Current therapeutic interventions and potential future ones, The importance of developing better diagnostic tools